Bahasa Inggris - Wulandari, Desi (http://jagadalimussirry.com/, 2019)
This study aims to determine the level of spiritual intelligence, the level of organizational commitment and to determine whether there is influence of spiritual intelligence on organizational commitment to the management of the Islamic Boarding School Boarding School BES Alimussirry. Using the SPSS 23 system and the research t-test technique, the results showed that the level of spiritual intelligence of the BES PPJA management resulted in 42.30% in the high category, 57.70% in the moderate category and 0% in the low category. The percentage for all member respondents is 80.30%, so the management's spiritual intelligence is included in the medium category. While the level of BES PPJA Management Organizational Commitment resulted in 50% in the high category, 50% in the medium category and 0% in the low category category. The percentage for all respondents is 49.73%, so the organizational commitment of the PPJA BES is in the moderate category. so there is an influence or relationship between spiritual intelligence on organizational commitment BES PPJA with the percentage influence of spiritual intelligence of 5% and the remaining 95% due to other factors not examined by researchers.